CYTOGENETIC ANALYSIS OF THE BRAZILIAN BLIND CATFISH PIMELODELLA-KRONEI AND ITS PRESUMED ANCESTOR, P-TRANSITORIA - Dealmeidatoledo, L. F.; Foresti, F.; Trajano, E.; Toledo, S. D. (Univ Florence Botany Inst, 1992)
Karyotypes of the blind catfish Pimelodella kronei from three different caves in the southwestern part of the State of São Paulo, Brazil, and of its presumed ancestor Pimelodella transitoria were examined. Chromosome number and formula, as well as C-banding pattern and NOR location were found to be the same in both species, supporting the hypothesis of a close relationship and even conspecificity of P. kronei and P. transitoria.
Keywords: BLIND CAVE FISHES; KARYOTYPE; SILURIFORMES; PIMELODIDAE